Fiscal Decentralization, Internal Control System, Accountability of Local Government and Audit Opinion - Rasmini, Ni Ketut; Masdiantini, Putu Riesty (Jurnal Ilmiah Akuntansi dan Bisnis, 2018)
The aim of this research is to examine the influence of fiscal decentralization and internal control system on the accountability of local government financial reporting with audit opinion in the previous year as the moderator variable. The research result shows that fiscal decentralization, which utilize the regional independency level and level of dependency towards the central government as proxy, does not influence the accountability of local government’s financial reporting. Meanwhile, internal control system, which utilizes the weakness of internal control system as proxy, has a negative effect on the accountability of local government financial reporting. The interaction test shows that audit opinion in the previous year is not able to strengthen the influence of the region’s level of independence , is unable to weaken the influence of the region’s level of dependence andis able to weaken the influence of internal control system on the accountability of local government financial reporting. Keywords:   Fiscal decentralization ; internal control system ; previous year audit opinion ; and accountability of financial reporting